Microbiome sharing between children, livestock and household surfaces in western Kenya. - Emily Mosites; Matt Sammons; Elkanah Otiang; Alexander Eng; Cecilia Noecker; Ohad Manor; Sarah Hilton; Samuel M Thumbi; Clayton Onyango; Gemina Garland-Lewis; Douglas R Call; M Kariuki Njenga; et al. (PLoS ONE)
The gut microbiome community structure and development are associated with several health outcomes in young children. To determine the household influences of gut microbiome structure, we assessed microbial sharing within households in western Kenya by sequencing 16S rRNA libraries of fecal samples from children and cattle, cloacal swabs from chickens, and swabs of household surfaces. Among the 156 households studied, children within the same household significantly shared their gut microbiome with each other, although we did not find significant sharing of gut microbiome across host species or household surfaces. Higher gut microbiome diversity among children was associated with lower wealth status and involvement in livestock feeding chores. Although more research is necessary to identify further drivers of microbiota development, these results suggest that the household should be considered as a unit. Livestock activities, health and microbiome perturbations among an individual child may have implications for other children in the household.